The heart is a lonely hunter [videorecording (DVD)] - Miller, Robert Ellis, 1932-; Arkin, Alan; Barrett, Laurinda; Keach, Stacy; McCullers, Carson, 1917-1967 (Distributed by Warner Home Video, 2008)
When deaf-mute John Singer moves to a sleepy Southern town to be near his hospitalized friend, a brain-damaged man-child, Singer's silent kindness draws to him others broken in body and spirit.